2020
DOI: 10.1002/anie.201914645
|View full text |Cite
|
Sign up to set email alerts
|

Tandem Insertion–[1,3]‐Rearrangement: Highly Enantioselective Construction of α‐Aminoketones

Abstract: An enantioselective synthesis of α‐aminoketone derivatives were readily available through a tandem insertion–[1,3] O‐to‐C rearrangement reaction. The rhodium salt and chiral N,N′‐dioxide‐indium(III) complex make up relay catalysis, which enables the O−H insertion of benzylic alcohols to N‐sulfonyl‐1,2,3‐triazoles, and asymmetric [1,3]‐rearrangement of amino enol ether intermediates, subsequently. Preliminary mechanistic studies suggested that the [1,3] O‐to‐C rearrangement step proceeded through an ion pair pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
22
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 59 publications
(22 citation statements)
references
References 91 publications
0
22
0
Order By: Relevance
“…70 These starting materials (94) can be subjected to an iridium-catalysed S N 2′ process with substituted amines (96) in the presence of asymmetric phosphonamidite ligand 95, resulting in enantioenriched protected α-amino ketones (97) in up to 96% yield with excellent regio-and stereoselectivity. Additionally, a wide range of aliphatic (98) and aromatic amines (99) were efficiently employed in this reaction, including peptide derivatives (100).…”
Section: Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…70 These starting materials (94) can be subjected to an iridium-catalysed S N 2′ process with substituted amines (96) in the presence of asymmetric phosphonamidite ligand 95, resulting in enantioenriched protected α-amino ketones (97) in up to 96% yield with excellent regio-and stereoselectivity. Additionally, a wide range of aliphatic (98) and aromatic amines (99) were efficiently employed in this reaction, including peptide derivatives (100).…”
Section: Reviewmentioning
confidence: 99%
“…This domino reaction was developed further by Dong and Feng, who reported an asymmetric [1,3]-rearrangement of the amino enol ether intermediate (Scheme 36). 98 Phenyl-substituted triazoles (167) were successfully reacted with a range of substituted-benzyl alcohols (168) in the presence of both rhodium and a chiral indium catalyst, and the corresponding α-substituted α-amino ketone products (170) were isolated in 72-93% yield and 82-96% ee for phenyl-substituted derivatives. Based on mechanistic studies, the authors proposed that the chiral N,N′-dioxide-indium(III) species coordinates to the enol ether oxygen, weakening the bond and blocking the Si face of the enolate.…”
Section: Reviewmentioning
confidence: 99%
“…Very recently, the same group also disclosed a parallel enantioselective synthesis of α-aminoketones 113 from Nsulfonyl-1,2,3-triazoles and benzyl alcohols 111 via dualcatalytic tandem OÀ H insertion followed by asymmetric [1,3]rearrangement reaction (Scheme 24). [43] A mixture of dirhodium catalyst and chiral N,N'-dioxide-indium(III) complex was used as asymmetric relay catalytic system to obtain several synthetically useful chiral α-aminoketones 113 in good to excellent yields and high enantioselectivities. However, electronically rich benzyl alcohols as well as heteroaryl substituted methanols were found to be less efficient and provided the corresponding products in relatively lower yields.…”
Section: Oà H Nà H Insertionmentioning
confidence: 99%
“…35 On the contrary, the analogous 1,3-shift process has encountered inevitable difficulties because of the disfavored four-membered cyclic transition state and no example of γ-boron migration has been reported. [36][37][38][39][40][41][42] Theoretical studies on such 1,3-boron migrating process has been concluded thermodynamically infavorable and experimentally inaccessible. 43 We envisioned that through consecutive boron-walking on carbon skeleton, the boronic ester moiety could switch to remote end of the allylic backbones for the formation of more stablized radical intermediates.…”
Section: Introductionmentioning
confidence: 99%